An investigation into Chinese EFL learners’ pragmatic competence - Rui Li,; Raja Rozina Raja Suleiman,; Azimah Sazalie, (Penerbit UKM, 2015)
Successful communication is influenced not only by language accuracy, but also by language appropriateness in various social contexts. Accordingly, second/foreign language (L2) learners‟ pragmatic competence as well as how they develop the competence has attracted much attention in the research field of interlanguage pragmatics (ILP). The existing literature on Chinese EFL learners‟ pragmatic competence focuses on their awareness of contextually appropriate language and neglects their production of the language. This study investigated Chinese EFL learners‟ pragmatic competence in terms of both awareness and production. Three research instruments were employed to collect data: a multiple-choice discourse completion task (MDCT), a written discourse completion task (WDCT), and a retrospective interview. Eight-five English major undergraduates from a university in China participated in the study. The results showed that Chinese EFL learners‟ ability to identify and produce contextually appropriate utterances needed to be promoted, and their pragmatic awareness was found to be positively correlated with their production. Compared with the ranking of imposition, Chinese EFL learners were more aware of the interlocutor‟s social power and tried to display the power distance in their language. However, they had difficulties in using appropriate strategies and linguistic features to achieve communicative intentions, and a very serious problem that they encountered was the intended meaning and force of different linguistic forms and strategies. The research findings provide evidence that Chinese EFL learners‟ pragmatic competence is still much influenced by Chinese language and culture, and some form of pragmatic instruction to raise their awareness or understanding of pragmatic features and force relation is crucial for the learning of L2 pragmatics.